Experimental study on the performance of fiber-reinforced laminated veneer lumber produced using Melia dubia for structural applications - Ramkumar V.R.; Anand N.; Prakash V.; Sujatha D.; Murali G. (Elsevier Ltd, 2025)
Melia dubia is a rapidly expanding tree species in southern India, but its main drawback has been limited use in wood-based panel products until recently. To address this research gap, this study aimed to develop three reinforcement materials for producing Reinforced Laminated Veneer Lumber (RLVL) using Melia dubia. Three types of reinforcement materials, chopped glass fiber mat (CGM), glass fiber mesh (GM), and bamboo mat (BM) were employed in two layers to manufacture RLVL. The investigated parameters included physical, mechanical, and bonding performance. Furthermore, morphological images were analyzed using optical and scanning electron microscopes. The research findings revealed that the highest performance was demonstrated by BM, followed by GM and CGM. These results suggest that all three reinforcements enhanced the mechanical properties and overall performance of RLVL. Arranging the reinforcement layers closer to the surface veneer layer in the assembly resulted in outstanding mechanical properties for RLVL. The performance is superior to solid wood made from the same wood species. The findings indicate that RLVL demonstrated superior mechanical properties to laminated veneer lumber (LVL) and solid wood. The modulus of rupture for LVL reinforced with CGM, GM and BM was 7.27%, 30.91%, and 32.73% greater respectively, than that of unreinforced LVL. The composite LVL reinforced with bamboo and glass matting exhibits potential for successful utilization in outdoor structural applications, including beams, rafters, and purlins. ? 2024 Elsevier Ltd